Characterisation of Sheet Masks with the Addition of Kemuning Leaf Extract (Murraya paniculata L.) - Azri Rahmadi; Emma Zaidar Nasution; Amir Hamzah Siregar; Rini Hardiyanti (Universitas Muhammadiyah Enrekang, 2023)
Research has been conducted on the use of kemuning leaves (murraya paniculate L.) in making sheet masks with formulations of kemuning leaf extract, chitosan, tapioca flour, and glycerin as facial smoothers. The results of the tensile strength test of sheet masks with preparations show that the tensile strength results of mask preparations without kemuning leaves are greater than the tensile strength using kemuning leaf extract and the results of the FTR test there is an absorption of wavenumber 3272.6 cm-1 -OH or –NH group, absorption at wavenumber 1640 cm-1 shows the presence of a C=O group meaning that in the process of making leaf sheet masks there is no chemical reaction, but only physical interaction. The results of the texture organoleptic test on the F5 sample are more dominantly preferred, the F0 sample is preferred in terms of color, and the F0 sample is preferred in terms of aroma, while in terms of general preference F0 is preferred by panelists. The pH test results on the six samples obtained pH results ranging from 6.12-6.29 categories are still safe to use marked by the pH value of cosmetic products allowed according to SNI ranging between 4.5-8.0. The antibacterial test results in the very strong category. The results of the antioxidant test are very strong and the results of measuring specific gravity show that the addition of kemuning leaf extract does not greatly affect the specific weight of a mask product. So that the use of kemuning leaves as a facial smoother is safe to use and has significant benefits.